Using the Service Quality approach, an analysis of customer satisfaction in early childhood education at Bina Mulia - Muhammad Khaerudin (International Journal of Information Technology and Computer Science Applications, 2023)
Kindergarten is an early childhood education facility, Bina Mulia Cibitung strives to attract and keep clients, specifically parents and guardians of students, by raising the standard of service in all areas. Increased customer satisfaction and trust, in this example from the person or guardian of pupils, are anticipated benefits of better service quality. Customers will be satisfied when their needs, wants, and expectations are met or exceeded during a transaction, leading to continued loyalty. Customer satisfaction is defined by research in this paper as a customer's reaction to a difference between the prior degree of importance and the actual performance he perceives after use. A service quality technique is used to gauge how satisfied customers are (customer satisfaction). This strategy makes use of a questionnaire as a tool to help determine what the customer's expectations are as well as their desires and impressions. Additionally, the difference between expectations and perceptions is used to gauge the quality of a service. Customer impressions of the service they actually receive and the service they expect can be compared to determine service quality.